Identification of Productivity Factors in Increasing Economic Resilience in West Java - Deti, Regina; Mohdari, Mohdari; Mantri, Yaya Mulya; Suharto, Imam; Yusuf, Ramayani (Fakultas Ekonomi Universitas Garut, 2023)
In employees’ daily activities, productivity is needed; productivity greatly influences the results desired by the company. This study aims to determine the factors affecting productivity to increase West Java's economic growth. Employees in the company will understand their goals, where, and how they match the company's goals. Thus these employees will be able to increase their productivity to achieve goals that are known together. This study uses a descriptive-qualitative research method by conducting descriptive, theoretical studies to collect, summarize and interpret data obtained from previous studies, journals and literature reviews. The results are then processed again to describe conditions or facts in the field to produce a clear, directed and comprehensive picture of the problems. The results shown are factors above 8: 1. Wages 2. Social security and Health 3. Skills and Work Experience 4. Motivation 5. Cooperation between employees 6. Career Path 7. Value and Rewards From the results of the FGD, 23 factors determine productivity. Of the 23 factors, 77 scored heavenly wages, social security and health, skills and work experience, motivation, employee cooperation, career paths, values and awards. By the theory put forward, factors supporting productivity